Dual-modal molecular imaging and therapeutic evaluation of coronary microvascular dysfunction using indocyanine green-doped targeted microbubbles. (8th March 2023) - Awen, Alimina; Hu, Dehong; Gao, Duyang; Wang, Zihang; Wu, Yayun; Zheng, Hairong; Guan, Lina; Mu, Yuming; Sheng, Zonghai
Abstract : We report ICG-doped targeted microbubbles as dual-modal probes for highly sensitive near-infrared fluorescence imaging and real-time ultrasound imaging of CMD in mouse models. Abstract : Coronary microvascular dysfunction (CMD), which causes a series of cardiovascular diseases, seriously endangers human health. However, precision diagnosis of CMD is still challenging due to the lack of sensitive probes and complementary imaging technologies. Herein, we demonstrate indocyanine green-doped targeted microbubbles (named T-MBs-ICG) as dual-modal probes for highly sensitive near-infrared (NIR) fluorescence imaging and high-resolution ultrasound imaging of CMD in mouse models. In vitro results show that T-MBs-ICG can specifically target fibrin, a specific CMD biomarker, via the cysteine–arginine–glutamate–lysine–alanine (CREKA) peptide modified on the surface of microbubbles. We further employ T-MBs-ICG to achieve NIR fluorescence imaging of injured myocardial tissue in a CMD mouse model, leading to a signal-to-background ratio (SBR) of up to 50, which is 20 fold higher than that of the non-targeted group. Furthermore, ultrasound molecular imaging of T-MBs-ICG is obtained within 60 s after intravenous injection, providing molecular information on ventricular and myocardial structures and fibrin with a resolution of 1.033 mm × 0.466 mm. More importantly, we utilize comprehensive dual-modal imaging of T-MBs-ICG to evaluate the therapeutic efficacy of rosuvastatin, a cardiovascular drug for the clinical treatment of CMD. Overall, the developed T-MBs-ICG probes with good biocompatibility exhibit great potential in the clinical diagnosis of CMD.